Professional Ethics and the Exemplary Behavior of Public Figures: A Literature Review from a Pancasila Perspective - Sukron Mazid; Delfiyan Widiyanto; Fazli Rachman; Imroatul Hasanah (Pancasila: Jurnal Keindonesiaan, 2025)
This literature review explores the relationship between professional ethics and exemplary behavior from the perspective of Pancasila values, which are relevant in addressing the complexities of modern professionalism. Various moral issues, such as abuse of authority, weak integrity, and the crisis of exemplary behavior, demand a stronger ethical foundation rooted in the nation's noble values. This study uses a conceptual approach based on literature with a critical analysis of the literature on professional ethics, Pancasila values, and the practice of exemplary behavior from figures. The novelty of this article lies in the integration of professional ethics with Pancasila, which is not only positioned as a normative guideline, but also synthesized into a conceptual model of Pancasila-based professional ethics that emphasizes the integration of moral values, social responsibility, and exemplary behavior from figures. The main synthesis of the study confirms that the revitalization of Pancasila values ​​strengthens the moral foundation of the profession while offering a practical ethical framework that is contextual, adaptive, and relevant to global challenges. The practical implications of this study are the importance of implementing Pancasila-based professional ethics in professional education, character development of the younger generation, and the development of ethical leadership capable of building a society with integrity, justice, and civility.